Weber’s Ideal Type and the Indonesian Historical Writing - Akhyat, Arif (History Department, Semarang State University and Historian Society of Indonesia, 2022)
This paper explains subject–object relations in Max Weber's idealist-structural concept. A sociologist and philosopher of history, Weber argued that social change cannot be separated from structural and dialectic thought as well as the ideal type behind its structural creations. Examining various historical cases offers a perspective on objectivity and subjectivity. Subject– object relations create dialectical relationships that reconstruct knowledge and awareness of historical reality. Historical reality, thus, is the final step in the creation of knowledge that comes from the subject. The paper seeks to understand how Weber's concept of ideal type has influenced historical philosophy in general and Indonesian historiography in particular. This article concludes that historians no longer simply describe and explain facts, but also provide alternative